Education on Assisted Reproductive Technology Program with Low Cost - Budihastuti, Uki Retno; Laqif, Abdurahman; Melinawati, Eriana; Prakosa, Teguh; Udiyanto, Hermawan; Priyanto, Heru; ., Darto; Ratnasari, Affi Angelia; Anggraeni, Asih; Wijayanti, Agung Sari (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Background: Assisted reproductive technology (ART) programs have proven to be a solution to help infertility couples to conceive. However, most couples face a financial crisis related to the relatively expensive cost of ART treatment. This service aims to educate about ART's meaning, direction, and procedures. Thus, couples want children to be able to understand the ART program at an affordable cost (low-cost) and undergo the ART program without any concerns about costs.Method: Seminar participants be given socialization in person and online through zoom software by the service provider. It is in two stages, in-person and online, so participants who cannot attend in person can follow this service program. In addition, participants are given a pre-test and post-test questions to assess their understanding of the ART program at an affordable cost.Result: The pre-test and post-test results were analyzed using Wilcoxon, which showed that after providing education about the ART program, the post-test results were significantly better than the pre-test results. Down value: 5.5%, fixed value: 15.2%, value rise: 79.3% with significance p<0.001.Conclusion: There are significant differences in the pre-test and post-test scores, which means that the participants understood the explanation the servicer gave.